Repositórios de dados científicos na América do Sul: uma análise da conformidade com os Princípios FAIR - Marcello Mundim Rodrigues (2020)
The growth of the digitization process in the world has presented challenges to the librarian practice, once traditionally its acting core is in the organization of bibliographic documents. The research had as an end studying the data phenomenon generated by the scientific process and the development of services that face the rising challenges of data management and curation, which involves volumes of digital resources in constant expansion. The research problem is on the environments and practices responsible for digital asset organization resulting from the contemporary scientific investigation. The study objects of such inquiry were: the data, as a phenomenon; the datasets, as informational unities; the FAIR Principles, as guidelines to the scientific data management and curation; and the institutional digital repositories of scientific data, as virtual environments of informational organization. The research questions answered were: What is the nature of the scientific datasets archived in the south american institutional digital repositories? What is the compliance of such repositories with the FAIR Principles? The research objective was to investigate scientific datasets and respective south american institutional digital repositories in light of the FAIR Principles. Dealing with the data phenomenon is assisting the academic community in its diverse fields, as well as the civil society in its digital and technological difficulties, providing more agile and assertive means of access in an increasingly nebulous and chaotic digital environment. The investigation consisted of an applied research, from the point of view of its nature; of a qualitative method research, by means of its approach to the problem; of an exploratory and analytical research, from the point of view of the objectives; of a bibliographic and documentary research, based on technical procedures. The scientific data repositories were surveyed in the RE3DATA database. The data collection was made by surveying articles in scientific databases, and by surveying data related to scientific datasets deposited in repositories linked to south american institutions. Content analysis was used to obtain the research results. The repositories found and suitable for investigation were those created and managed by the following institutions: PPBio (Brazil); UFPR (Brazil); CIAT (Colombia); PUC (Peru); MEC (Peru); and USIL (Peru). The findings indicate that the software behind the investigated repositories which are fit to management and curation of scientific data are Morpho (DataONE), DSpace, and Dataverse. Regarding the investigated scientific datasets, it was noted that their nature is clustered in textual and numerical data, saved in text files and tables, respectively. The repositories in greater compliance with the FAIR Principles were established by the use of Dataverse. It was concluded that information professionals should seek their training in data, starting with the planning of projects and institutional policies aimed at the implementation of scientific data repositories, including the understanding of the divergent needs among communities, the technical computational knowledge required for such practices, and ideally, the search for standardization and maintenance of these services.